Descending thoracic aorta to bifemoral bypass grafting in Aortobiiliac occlusive disease - Suraj Wasudeo Nagre (Journal of Cardiovascular Medicine and Cardiology - Peertechz Publications, 2020)
Introduction: The aim of this prospective study is to describe the clinical symptoms, investigation findings and surgical treatment of aortoiliac occlusive disease where abdominal approach not feasible or not possible for aortobifemoral bypass grafting. Method: From May 2013 to May 2019, ten patients were treated with descending thoracic aorto-bifemoral bypass for aortoiliac occlusive disease at Grant Medical College and JJ group of Hospitals, Mumbai (Maharashtra). Total 20 limbs were re-vascularized. Demographic data, co-morbid factors, per operative findings were noted. Indication for surgery is juxtarenal occlusion of the abdominal aorta, in most of the cases. In postoperative period, all patients were evaluated for appearance of distal pulsations, primary patency, warmness of foot, symptom relief, wound infection, healing of the ulcer, and complications. CT angiography was done in follow-up. Maximal followup of two years and minimum followup of one month was done after surgery. Results: No mortality. Mean duration of surgery was 2.5-5 h and mean blood loss was 250 - 400 mL. Major morbidity includes one graft occlusion. None of the patients developed proximal propagation of aortic thrombus. Ulcers showed healing. All patients had a good quality of life postoperatively. Postoperative angiography showed good re-vascularization. Conclusion: Majority of our patients are old age having juxtarenal aortic occlusion so we decided to use DTA as inflow for primary revascularization to avoid entering abdomen and renal injury. Some authors have recommended supraceliac aorta bypass surgery within the retroperitoneal space for juxtarenal aortic occlusive disease but is technically difficult and associated with morbidity. The major limitation to thoracic aorta bifemoral grafting technique is the morbidity rate associated with thoracotomy in a relatively high-risk vascular surgery population. Also, tunnelling in conventional DTA-to-femoral artery bypass is usually a "blind" procedure.For the cardiothoracic surgeon with experience, the use of descending thoracic aorta could be a very good alternative for infrarenal aortic occlusion or extra-anatomic aortoiliac bypass without any morbidity and mortality with good improvement in quality of life.